Structural Characterization of Salts Using X-ray Fluorescence Technique: Experiments on Samples Collected from Kurdistan Region of Iraq - Meena, Bashdar I.; Karim, Hawbash H.; Aziz, Kurdistan F.; Chaqmaqchee, Faten A.; Kokhasmail , Dashne M.; Hussein, Khabat N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This study investigates the structure of 21 table salts that were collected from different local markets in the Kurdistan region of Iraq. The major trace elements and iodine concentrations in tablesalt are analyzed through the X-ray fluorescence (XRF) technique and the titration method, respectively. The study shows that using XRF spectral analysis, the collected table salt samples are rich in chlorine, sodium, and contain a lower percentage of bromine, strontium, tin, tellurium, and iodine. Moreover, these samples have a high percentage of sulfur and sirconium, where the molybdenum is >0.2%. Other elements such as zinc and copper are essential and found in low concentrations <0.0086% and 0.001%. Iodine is a trace element that is necessary nutrients for human life, and it is naturally present in some foods. Iodine deficiency is brought on by a lack of iodine consumption. Iodized salt is highly recommended as a source of iodine to prevent iodine deficiency disease. Iodine is added to table salt in two different ways, either through iodate or through iodine. The results show that only 25% of the salt samples have an adequate level of iodine, while the other samples have low or no iodine content. According to the World Health Organization, quality of salt depends on iodine concentration and other trace elements, which are necessary for human health.